Australian aboriginal and torres strait islanders' mental health issues: A litany of social causation - Mrigendra Das; Ranjit Kini; Gagan Garg; Robert Parker (Indian Journal of Social Psychiatry, 2018)
The Aboriginal and Torres Strait Islanders (ATSI) are the Indigenous people of Australia and constitute 3.3% of the Australian population, having been present in the country for more than 50,000 years before the colonization of Australia in 1788. Aboriginal culture/society is structured around the community, with strong kinship, belief systems, family ties, and networks. The colonization of Australia led to significant adversities for the ATSI population with loss of traditional way of life, land, and resources; marginalization, poverty, and being subject to racism and policies such as the “stolen generations” causing intergenerational trauma. These factors are considered as substrates for the subsequent increase in mental health and other health issues. ATSI people have poorer outcomes compared to other Australians in areas of physical health and life expectancy. They have higher rates of mental illness, suicide, alcohol/substance misuse, incarceration, and being subject to violence. Epidemiological research is lacking in ATSI population because of methodological difficulties. There are government policies/initiatives to reduce the disparity, which has been slow to bear results. The concepts of cultural safety and competence are important in the clinical management of ATSI population. Clinical presentation/management can be different in this group, and there is a need for more clinical guidelines. There have been a number of innovative strategies to improve mental illness outcomes. The paper illustrates the psychosocial impact of colonization on the ATSI population. There is an urgent need for research to understand and address the core issues that drive health inequalities in this group of disadvantaged Australians.